Respostas

A melhor resposta!
2014-03-23T19:32:15-03:00
(x+5).(x-3)= 0
x² -3x + 5x - 15 = 0
x² + 2x - 15 = 0 ~> a = 1 , b = 2 , c = -15

Δ = b² - 4ac
Δ = 2² - 4.1.(-15)
Δ = 4 - (-60)
Δ = 64 

x = -b 
± √Δ
         2a

x = -2 
± √64
         2.1

x = -2 
± 8
         2

x' = -2 + 8 = 6 = 3              x" = -2 - 8 = -10 = -5
         2        2                              2        2


S = {-5 ; 3 } 
3 5 3
2014-03-23T19:32:45-03:00
(x+5) (x-3)=0x^2-3x+5x-15
x^2+2x-15
b^2-4ac
(2)^2-4.1(-15)
4+60=64
1Δ=3
2Δ=-5

1 5 1